Decision of the board of directors of the authority No. 60 of the year 2017 on licensing the companies to combine several financing activities (Financial lease, Real state financing, factoring) and the controls of practicing more than one activity / The Egyptian Financial Supervisory Authority ; Translated by The middle east library for economic services. - The Egyptian Financial Supervisory Authority; The middle east library for economic services, translator. (2025)
Serial No. 26/2017